Role and Purpose of Project Sketching in Design - Malkhasyan, Knkush; Arakelyan, Ani (Scientific Papers of National University of Architecture and Construction of Armenia, 2023)
The article considers the significance and importance of project sketching in the field of design. The process of origin and formation of sketching as a unique branch is described. The article aims to explore examples of sketching in different fields and to appreciate their role and purpose through analysis. The importance of sketching in the creative and design processes is highlighted. The effectiveness of developing cognitive and motor skills through sketching is addressed. The use of sketching techniques is considered not only in education but also in scientific and medical fields as an effective method of brain training and the development of motor skills. There are also comments on the progress of sketching, based on the analysis of which new solutions are proposed. Reference is also made to the materials and methods used in sketching. The article can serve as educational material for students and professionals studying the field.